︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎
выражаем у: у=10-7х, подставляем в 1-е уравнение: 2х-3(10-7х)=16 отсюда находим х, х=2. Подставим х в вырадение у=10-7х: у=10-7*2=-4.
х=2, у=-4
ответ: (2; -4)